TAHLILU MAWAD AD DIRASIYAH FI KITAB AL ARABIYAH AL MUFRIHAH - NI'matun Najah (UIN ANTASARI, 2019)
Good material and appropriate books, as needed, will help the students and the teacher while teaching. The Arabic Language Development Unit Program is obligatory for all university students at the State Islamic University of Antasari in Banjarmasin. This program is one of the conditions for obtaining a bachelor's degree. This research aims to analyze the book